Pengaruh Kualitas Produk, Harga dan Suasana Tempat terhadap Kepuasan Konsumen pada WR. Gado-Gado Maya - Gunawan, Indra; Dwikotjo Sri Sumantyo, Franciscus; Ali, Hapzi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
Abstract: This study aims to determine the effect of product quality, price, and atmosphere of the place on consumer satisfaction. The author approaches with a quantitative method towards consumers of Gado-Gado Maya visitors. The population will be consumers who visit by making purchases at “Wr. Gado-Gado Maya